Kehidupan Ekonomi, Sosial, dan Kesehatan Lansia dalam Pengasuhan Keluarga di Lingkungan IV Galang Kota - Ricco Habil; Berlianti Berlianti (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2023)
This study aims to look at the facts in the field regarding the life of the elderly in family care. The research location is in Environment IV Galang Kota, Galang District, Deli Serdang Regency. Data collection techniques with literature study, in-depth interviews, observation and documentation. Data obtained in the field were then analyzed by researchers who were described qualitatively. This type of research uses a qualitative descriptive method that describes the facts in the field in depth. The results of the study show that the life of the elderly is still relatively good. Based on three indicators, namely: social life, economy and health of the elderly. Social life indicators consist of two, namely: family and community interactions. Overall good family interaction because active communication. Community interaction is not good because the condition of the elderly does not allow them to carry out activities with the community. Indicators of economic life are: finance, income and consumption. Finances cannot be seen because the finances of the elderly are managed by children who care for and mix with family finances. The income of the elderly is not good because the elderly are not working. Consumption of the elderly is good because the family can meet all the consumption needs of the elderly. Elderly health indicators are: physical, mental and social health. The physical health of the elderly as a whole is not good because the elderly experience various physical health problems. Overall mental health is good, except for one elderly showing symptoms of depression. The social health of the elderly as a whole is not good because of the condition of the elderly which is difficult to build relationships with the community environment. Kata Kunci: Lansia, kehidupan lansia, pengasuhan keluarga.